Advancement in modern breeding and genomic approaches to accelerate rice improvement: speed breeding focus - Zainuddin, Fatin’Alyaa; Ismail, Mohd Razi; Md Hatta, Muhammad Asyraf; Ramlee, Shairul Izan (Springer Science and Business Media B.V., 2024)
Rice (Oryza sativa L.) is a common staple food widely cultivated and consumed globally. The increase in world population and slow genetic gain in rice production in the face of a rapidly evolving climate could cause food scarcity and decreased crop productivity. It is crucial to expedite the development and release of climate-resilient crop varieties through selective breeding and improvement to mitigate the impact of climate change. Speed breeding has emerged as a promising tool for rice breeding, offering the potential to accelerate the generation time. By streamlining the breeding process and reducing the time taken for each generation, speed breeding empowers breeders to screen for desired traits rapidly and efficiently, enhancing the selection and development of improved rice varieties to meet the growing global demand for food. This review focuses on the applications of speed breeding technology to accelerate rice breeding and further highlights the critical factors for speed breeding development in rice production, such as temperature, humidity, light, and genetic diversity. Understanding and optimizing these factors is vital in successfully implementing speed breeding technology in developing robust, high-yielding, and climate-resilient rice varieties for feeding the future.